Marianna Ritchey, Composing Capital: Classical Music in the Neoliberal Era (2019) (Journal of the Society for Musicology in Ireland, 2020)
A review of Marianna Ritchey, Composing Capital: Classical Music in the Neoliberal Era (Chicago, London: The University of Chicago Press, 2019). ISBN 9780226640235